THU0262 Identifying patients with axial spondyloarthritis from a cohort of patients with chronic back pain in orthopaedics care (AWARE STUDY). (12th June 2018) - Braun, J.; Mosch, T.; Fischer, I.; Kiltz, U.
Abstract : Background: Making an early diagnosis of axial spondyloarthritis (axSpA) has remained a challenge. The combination of clinical items suggestive of inflammatory back pain has proved useful for early identification of patients with axSpA in a pilot study in primary care. 1 It has been shown that at least three of five features have a high prognostic impact. Objectives: To evaluate the performance of these 5 clinical items (called AWARE criteria) to identify patients with axSpA from a large cohort of patients with chronic back pain in orthopaedics care. Methods: In a dult patients with chronic back pain (>3 months) and age at onset of symptoms<45 years. who were concerned for referral to rheumatologists, the AWARE criteria were assessed and documented prior referring to the rheumatologists. Results: A total of 1306 patients (pts) first seen by orthopaedic surgeons were included. Of those, 500 pts were also seen by rheumatologists, and 188 (37.6%) were diagnosed as axSpA, and, amongst others, 52.2% with non-specific back pain by clinical judgment. A total of 87 cases (17.4%) were diagnosed with ankylosing spondylitis (AS) and 101 (20.2%) with non-radiographic axSpA. A total of 206 pts fulfilled the ASAS classification criteria. The mean age of patients with axSpA was 38±11.5 years, 46.2% were male, the mean duration of back pain was 94.1±103.6 months. The AWARE criteria had a sensitivity and specificity of 93.6% and 17.0% if ≥3 criteria were chosen, and 6.3% and 83.0% with <3 criteria. In axSpA vs. non-axSpA pts, imaging (MRI or x-ray) was positive in 90.6% vs 9.4%, HLA B27 in 69.4% vs 30.6%, 57.6% vs. 42.1% had a good response to NSAIDS, and an elevated CRP in 70.1% vs. 29.9%. A minority of axSpA patients had arthritis (5.6%), enthesitis (6.2%), dactylitis (1%), uveitis (3.8%), psoriasis (4.8%) and IBD (3.6%). Positive imaging (MRI or x-ray) resulted in the highest likelihood ratio (LR) for a diagnosis of axSpA. In combination with HLA B27 +the LR was highest (127.1). Conclusions: Even though the procedure of how patients were preselected in this study caused a selection bias for statistical analyses we think that this study confirms the usefulness of the original AWARE criteria to improve the identification of young patients with chronic back pain in primary care. The important role of imaging and HLA B27 was confirmed. In future studies the two-step approach with three clinical question first and then HLA B27 testing if necessary will be further investigated. Reference: [1] Braun A, et al. Ann Rheum Dis2011Oct;70(10):1782–1787. Disclosure of Interest: J. Braun Consultant for: AbbVie, Amgen, Biogen, Boehringer Ingelheim, BMS, Celgene, Celltrion, Centocor, Chugai, Epirus, Hospira, Janssen, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis, UCB., Speakers bureau: AbbVie, Amgen, Biogen, Boehringer Ingelheim, BMS, Celgene, Celltrion, Centocor, Chugai, EBEWE Pharma, Epirus, Hospira, Janssen, Medac, MSD (Schering-Plough), Mundipharma, Novartis, Pfizer (Wyeth), Roche, Sanofi-Aventis and UCB., T. Mosch Shareholder of: AbbVie Deutschland GmbH and Co. KG, Employee of: AbbVie Deutschland GmbH and Co. KG, I. Fischer Consultant for: AbbVie Deutschland GmbH and Co. KG, U. Kiltz Consultant for: AbbVie, Chugai, Grünenthal, Janssen, MSD, Novartis, Pfizer, Roche and UCB., Speakers bureau: AbbVie, Chugai, Grünenthal, Janssen, MSD, Novartis, Pfizer, Roche and UCB.